FDI, International Trade and Union Collusion - Domenico Buccella (FIW - Research Centre International Economics, 2010)
This paper deals with firms' decision related to international activities in a twocountry oligopoly model with a homogeneous product and unionized labor markets. Using a three-stage non-cooperative game with firms being first movers, it is found that firms' strategies are affected by the scale of fixed costs of direct investments, trade costs and union wage strategies in labor markets, giving rise to different productive structures in equilibrium. Scopes and incentives for unions' collusion are analyzed. The consequences on national welfare levels of both unions and firms' strategic behavior are also investigated, deriving some policy insights.
Keywords: F16; F21; F23; J51; L13; 330; Foreign Direct Investment; International trade; Collusion; Labor unions